Effects of transplanting and AMF inoculation on the fruit yield of African eggplants (Solanum aethiopicum and Solanum anguivi) in Tanzania - Xu, Xiangming; Dinssa, Fekadu Fufa; Minja, Ruth; Mwaijande, Violeth; Mbwambo, Omary; Mziray, Zainab; Stavridou, Eleftheria; Bishop, Gerard J. (Frontiers in Agronomy, 2023)
The African eggplant (Solanum aethiopicum L., Gilo group) is one of the most common traditional vegetables in Tanzania. The yield of the African eggplant in Tanzania is far lower than the potential yield expected, which is due primarily to biotic and abiotic stresses. We conducted experiments at two locations in Tanzania to study whether or not plant growth and the fruit yield of the Gilo group of African eggplant can be significantly improved through transplanting coupled with the inoculation of arbuscular mycorrhizal fungi (AMF) at sowing. Many plants, particularly for the directly sown treatment, died well before harvesting, and, in addition, many surviving plants showed symptoms of wilting. The transplanting of tray seedlings and using AMF inocula at sowing led to an overall significant increase in fruit yield by 30%–40% and 20%–25%, respectively. Increased fruit yield per experimental plot resulted primarily from a greater number of plants that survived and reached the harvesting stage. The exact effect of planting method (i.e., transplanting or direct sowing) and AMF inoculation, however, varied greatly with plant accessions. Further research is needed to understand the cause(s) for plant mortality in order to develop appropriate plant management practices.